THE RELATIONSHIP OF STAFF JOB SATISFACTION AND INTENTION TO LEAVE AT A HOSPITAL - Nimas Ayu Mashuri; Diajeng Puspa Arum Maharani (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2019)
Background: Job dissatisfaction arises as a result of a mismatch between expectation and reality in the employment conditions of employees in an organization. Job dissatisfaction can lead to the intention of to leave. Employees with Intention to leave have the opportunity to do turnover of their organization.Aims: The purpose of this study is to determine the relationship between job satisfaction variable and intention to leave variable.Methods: This study used quantitative method with cross-sectional design. The samples were 52 staffs of the Surabaya Orthopaedic and Traumatology Hospital who were still actively working until June 2012. Job satisfaction variable was measured using a questionnaire research instrument called Job Satisfaction Survey (JSS) by Spector while the intention to leave variable was measured using a questionnaire research instrument that is made by researchers.Results: The results of this study indicate that the level of staff work satisfaction of Surabaya Orthopaedic and Traumatology Hospital is relatively high while the intention to leave is moderate. The results of the Spearman Correlation show a number of -0.314 which shows a correlation that is not unidirectional and significant between the two variables. This means that job satisfaction and intention to leave have a negative relationship so that the higher the job satisfaction is, the lower the intention to leave is.Conclusion: It can be concluded from the study that job satisfaction has a significant relationship and is not in line with the intention to leave of the staffs. Therefore, it is important for the Surabaya Orthopaedic and Traumatology Hospital to improve their staff job satisfaction thus the staff loyalty can be formed. Keywords: Job satisfaction, Intention to leave, Hospital staff.